The first‐in‐man randomized trial of a beta3 adrenoceptor agonist in chronic heart failure: the BEAT‐HF trial. (18th December 2016) - Bundgaard, Henning; Axelsson, Anna; Hartvig Thomsen, Jakob; Sørgaard, Mathias; Kofoed, Klaus F.; Hasselbalch, Rasmus; Fry, Natasha A.S.; Valeur, Nana; Boesgaard, Søren; Gustafsson, Finn; Køber, Lars; Iversen, Kasper; et al.
Abstract: Aims: The third isotype of beta adrenergic receptors (β3 ARs) has distinctly different effects on cardiomyocytes compared with β1 and β2 ARs. Stimulation of β3 ARs may reduce cardiomyocyte Na + overload and reduce oxidative stress in heart failure (HF). We examined if treatment with the β3 AR agonist mirabegron increases LVEF in patients with HF. Methods and results: In a double‐blind trial we randomly assigned 70 patients with NYHA class II–III HF and LVEF <40% at screening–echocardiography to receive mirabegron or placebo for 6 months as add‐on to optimized standard therapy. The primary endpoint was an increase in LVEF after 6 months as measured by computed tomography (CT). Changes in LVEF after 6 months between treatment groups were not significantly different (0.4%, −3.5 to 3.8%, P = 0.82). In an exploratory analysis, based on an expectation that the pathophysiological substrate targeted with treatment is dependent on the baseline LVEF, patients with LVEF <40% by CT given mirabegron had a significant increase in LVEF while no increase was seen in patients given placebo. The changes were significantly different between groups (5.5%, 0.6–10.4%, P < 0.03). Additionally, there was interaction between baseline LVEF and change in LVEF in the entire group of patients treated with mirabegron ( R 2 = 0.40, β = −0.63, P < 0.001), but not in the placebo group ( R 2 = 0.00, β = −0.01, P = 0.95). Treatment was generally well tolerated. Three patients in each group had fatal or life‐threatening events. Conclusions: The primary endpoint was not reached. Exploratory analysis indicated that β3 AR stimulation by mirabegron increased LVEF in patients with severe HF. Treatment appeared safe. Additional studies in severe HF are needed. Trial registration: NCT01876433